2019
DOI: 10.1021/acs.jpcc.9b09203
|View full text |Cite
|
Sign up to set email alerts
|

Combined Experimental and Theoretical Study of Cobalt Corroles as Catalysts for Oxygen Reduction Reaction

Abstract: Bioinspired transition-metal complexes may serve as efficient and low-cost potential catalysts for oxygen reduction reaction (ORR) in fuel cells, instead of precious group metal-free (PGM-free) materials. Herein, we present a study of the ORR electrocatalytic activity of different mesosubstituted Co-corroles with varying electronegativity using both experimental and theoretical methods. Specifically, we studied the influence of different mesosubstituted Co-corroles on catalytic activity. Using density function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 52 publications
(81 reference statements)
1
20
0
Order By: Relevance
“…Next, the number ( n ) of electrons transferred per O 2 molecule with 1 /CNT was determined to be 3.97 based on RRDE results, while it was 3.84 with 2 /CNT (Figure 3 b). Similar n values were obtained by using Koutecky–Levich (K–L) analyses (Figures S24, S25) [60, 61] . The durability of 1 /CNT was then evaluated, showing almost no loss of electrocatalytic ORR activity after 1000 CV cycles (Figure 3 c).…”
Section: Figuresupporting
confidence: 71%
See 1 more Smart Citation
“…Next, the number ( n ) of electrons transferred per O 2 molecule with 1 /CNT was determined to be 3.97 based on RRDE results, while it was 3.84 with 2 /CNT (Figure 3 b). Similar n values were obtained by using Koutecky–Levich (K–L) analyses (Figures S24, S25) [60, 61] . The durability of 1 /CNT was then evaluated, showing almost no loss of electrocatalytic ORR activity after 1000 CV cycles (Figure 3 c).…”
Section: Figuresupporting
confidence: 71%
“…Similar n values were obtained by using Koutecky-Levich (K-L) analyses ( Figures S24, S25). [60,61] The durability of 1/ CNT was then evaluated, showing almost no loss of electrocatalytic ORR activity after 1000 CV cycles (Figure 3 c). In prolonged electrolysis, the catalytic ORR current with 1/CNT dropped only by < 6 % after 10 h ( Figure S26).…”
Section: Chemiementioning
confidence: 99%
“…In the past few years, we have investigated the catalytic activity of metallo‐corroles towards ORR in acidic and alkaline media [14–21] . In these studies, different metal centers and substituents were introduced to the corroles ring.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the stability of high‐valent metal–oxo intermediates greatly affects the catalytic performance of ORR. [ 95–97 ] The corrole ring exhibits three protons instead of two, which allows corrole to stabilize high‐oxidation‐state transition metals. Recent studies on metal corroles have found that when the central metal ion was Co(III), the catalyst exhibited the highest ORR activity.…”
Section: Carbon Nanotube/mmc Orr Catalystsmentioning
confidence: 99%
“…The various substituents on the macrocyclic ligand and the electron‐donating, electron‐withdrawing, and π‐conjugated characteristics of the fifth axial ligand can adjust the electron‐cloud density of the central metal ion, thereby indirectly affecting the interaction between the central metal ion and the reaction intermediates. [ 69,77,81,94–97,124,128 ] Owing to the difference in ring size, the best porphyrin and phthalocyanine ORR performance was obtained when the central metal ion was cobalt and iron, respectively. The phthalocyanine ligand can provide more electrons to the central Fe ion than porphyrin can, which weakens the iron's oxygen adsorption.…”
Section: Guidelines For Developing Mmc‐functionalized Carbon‐based Orr Electrocatalystsmentioning
confidence: 99%